Big City Health Officials' Conceptualizations of Health Equity. Issue 4 (July 2019) - Henson, Rosie Mae; McGinty, Meghan; Juliano, Chrissie; Purtle, Jonathan
Abstract : Context: Senior health officials of local health departments are uniquely positioned to provide transformational leadership on health disparities and inequities. Objective: This study aimed to understand how senior health officials in large US cities define health equity and its relationship with disparities and characterize these senior health officials' perceptions of using health equity and disparity language in local public health practice. Design: In 2016, we used a general inductive qualitative design and conducted 23 semistructured interviews with leaders of large local health departments. Thematic content analysis was conducted using NVivo 11. Participants: A purposive sample of senior health officials from Big Cities Health Coalition cities. Results: Health equity was conceptualized fairly consistently among senior health officials in big cities. Core elements of these conceptualizations include social and economic conditions, the input and redistribution of resources, equity in practice, values of justice and fairness, and equity as an outcome to be achieved. Senior health officials saw health disparity and health inequity as distinct but related concepts. Relationships between concepts included disparities data to identify and prioritize inequities, inequities creating health disparities, health equity to eliminate disparities, and disparities becoming inequities when their root causes are unjust. Some respondents critiqued health equity terminology for representing a superficial change, being inaccessible, and being politically loaded. Conclusions: Understanding how senior health officials conceptualize health equity and disparities can focus policy priorities, resources, and the scope of work undertaken by local health departments. Having a common language for health equity allows for policy and resource advocacy to promote the health of marginalized populations. Abstract : Supplemental Digital Content is Available in the Text.